Impact of Demonetization on the Return of Selected Indian Banking Stocks - Kaur, Harpreet; Singh, Ravinderjit (Indian Journal of Research in Capital Markets, 2018)
Demonetization was the act of discontinuing a currency unit of its status as legal tender and replacing it with a new currency. It is an instrument used not only to tackle various economic problems such as corruption, inflation, tax evasion, etc., but also helps in converting a cash-dependent economy into cashless economy. To achieve these objectives, a move was taken by the Indian government on November 8, 2016 to demonetize high denomination currencies that affected various sectors of the Indian economy. Therefore, an attempt was made to examine the impact of demonetization on the Indian banking sector by applying the event study methodology on the stock prices of selected Indian banks in the year 2016. The study found that in the pre-announcement period, some of the banking stocks had significant positive abnormal returns. On the actual date of announcement, among 16 selected banks, 15 banks reacted positively to news. Thus, the demonetization announcement in India had a significant impact on the share prices of selected banking companies.